Gambaran Tingkat Stres Kerja Pada Petugas Lembaga Pemasyarakatan Kelas IIA Garut - Della Herliawati; Dadang Purnama; Nur Oktavia Hidayati (Universitas Malahayati Lampung, 2026)
ABSTRACT Mental health in the workplace is an important aspect in maintaining the well-being and productivity of officers, especially for those working in high-pressure environments such as correctional institutions. Correctional officers often face tight time pressures, high workloads, and high risks that can trigger anxiety and increase work stress. This study to determine the level of work stress among officers at the Class II A Garut Correctional Institution. Using quantitative descriptive design. The study population was all officers of Class II A Garut Correctional Institution, totaling 84 respondents, using total sampling technique. Data were collected through Job Stress Scale questionnaires that had been translated into Indonesian, then analyzed descriptively using frequency distribution and percentage.The majority of respondents were in the mild work stress category, as many as 46 people (54.8%), then the moderate work stress category as many as 34 people (40.5%), and the high work stress category as many as 4 people (4.8%). Most officers of Class II A Garut Correctional Institution experienced mild work stress based on the dimensions of time pressure and anxiety. However, there were still officers with moderate to high levels of stress, indicating the need for attention to the mental health of Correctional Institution officers. Keywords: Work Stress, Time Pressure, Anxiety, Correctional Officers. ABSTRAK Kesehatan mental di tempat kerja merupakan aspek penting dalam menjaga kesejahteraan dan produktivitas petugas, khususnya bagi mereka yang bekerja dalam lingkungan dengan tekanan tinggi seperti Lembaga Pemasyarakatan. Petugas Lembaga Pemasyarakatan sering menghadapi tekanan waktu yang ketat, beban kerja yang tinggi, serta tingginya risiko yang dapat memicu kecemasan dan meningkatkan stres kerja. Penelitian ini bertujuan untuk mengetahui gambaran tingkat stres kerja pada petugas Lembaga Pemasyarakatan Kelas IIA Garut. Penelitian ini menggunakan desain kuantitatif deskriptif dengan pendekatan cross-sectional. Teknik pengambilan sampel menggunakan total sampling dengan jumlah responden sebanyak 84 orang. Instrumen penelitian berupa kuesioner stres kerja yang dianalisis secara deskriptif menggunakan distribusi frekuensi dan persentase. Mayoritas responden berada pada kategori stres kerja ringan sebanyak 46 orang (54,8%), kemudian kategori stres kerja sedang sebanyak 34 orang (40,5%), dan kategori stres kerja tinggi sebanyak 4 orang (4,8%). Sebagian besar petugas Lembaga Pemasyarakatan Kelas II A Garut mengalami stres kerja kategori ringan berdasarkan dimensi tekanan waktu dan kecemasan. Namun, masih terdapat petugas dengan tingkat akhir stres sedang hingga tinggi yang menunjukkan perlunya perhatian terhadap kesehatan mental petugas Lembaga Pemasyarakatan. Kata Kunci: Stres Kerja, Tekanan Waktu, Kecemasan, Petugas Lembaga Pemasyarakatan.